Factors Underlying Individual Differences in Speech-Recognition Threshold (SRT) in Noise Among Older Adults - Humes, Larry E. (Frontiers in Aging Neuroscience, 2021)
Many older adults have difficulty understanding speech in noisy backgrounds. In this study, we examined peripheral auditory, higher-level auditory, and cognitive factors that may contribute to such difficulties. A convenience sample of 137 volunteer older adults, 90 women, and 47 men, ranging in age from 47 to 94 years (M = 69.2 and SD = 10.1 years) completed a large battery of tests. Auditory tests included measures of pure-tone threshold, clinical and psychophysical, as well as two measures of gap-detection threshold and four measures of temporal-order identification. The latter included two monaural and two dichotic listening conditions. In addition, cognition was assessed using the complete Wechsler Adult Intelligence Scale-3rd Edition (WAIS-III). Two monaural measures of speech-recognition threshold (SRT) in noise, the QuickSIN, and the WIN, were obtained from each ear at relatively high presentation levels of 93 or 103 dB SPL to minimize audibility concerns. Group data, both aggregate and by age decade, were evaluated initially to allow comparison to data in the literature. Next, following the application of principal-components factor analysis for data reduction, individual differences in speech-recognition-in-noise performance were examined using multiple-linear-regression analyses. Excellent fits were obtained, accounting for 60–77% of the total variance, with most accounted for by the audibility of the speech and noise stimuli and the severity of hearing loss with the balance primarily associated with cognitive function.